UNPACKING THE COMPLEXITIES OF TURKISH-GREEK GEOPOLITICAL COMPETITION AND ITS EFFECT ON EASTERN MEDITERRANEAN REGION - Suleyman, Karimi, Ph.D; Javad, Düvell (International Journal of Allied Sciences (IJAS), 2023)
The Mediterranean Basin, which comprises the Mediterranean Sea, its islands, and adjacent continental regions, is the primary arena for the ongoing competition between Turkey and Greece. This analysis examined potential factors behind the geopolitical rivalries in the Eastern Mediterranean. Our findings suggest that historical confrontations, such as the Greek defiance against the Ottoman Turks and the Turkish resistance to Greek occupiers, disputes over territorial waters, islands, and energy resources, minority rights concerns, Greek backing of Turkish opposition, and unlawful border crossings all contribute to the rivalry between the two countries. Therefore, due to the significance of geographical factors in the contest between Turkey and Greece, resolving these disputes presents a daunting and time-consuming challenge